IMPROVING STORY LISTENING SKILLS OF CLASS 5 STUDENTS THROUGH THE WORD SQUARE LEARNING METHOD - Sri Defi; Agung Setyawan; Mohamad Usman; Moh Rahbini (Citra Dharma Cindekia, 2022)
Listening skill is one of the important skills that every individual has. Listening skills are also part of increasing student literacy. However, in the learning process it will be difficult to improve these skills if students do not have an interest in learning. The purpose of classroom action research is to increase students' interest in learning and listening to stories through the Word Square learning model. This type of research is classroom action research using the Kemmis and Mc Tanggart Model. Qualitative descriptive data analysis techniques with data collection techniques through observation and written tests. The research subjects were fifth grade students at UPTD SDN Banyuajuh 6, Kamal District, Bangkalan Regency. with the results of the study an average pre-cycle score of 53 (Low), cycle I 78 (Medium), and cycle II 98 (High). Shows the influence of the success of the Word Square learning method in increasing learning interest and story listening skills. Based on the results of these data it can be concluded that the use of the word square method can improve the listening skills of class V students at the UPTD SDN Banyuajuh 6, Kamal District, Bangkalan Regency